Shots fired: gun violence in the United States - Rahtz, Howard (Lynne Rienner Publishers, 2020)
Mass killings. Gang violence. Street crimes. Suicides. Accidental shootings. The United States is enduring a literal epidemic of gun violence. Howard Rahtz, drawing on decades of experience as a police officer all too familiar with the horrors that guns can cause, delves deeply into the nature and impact of this epidemic. Rahtz explores each element of the triangle of ability, desire, and opportunity that typically characterizes gun violence. Going further, he also suggests practical, "left of bang" preventative actions--steps that could limit the violence while respecting contentious Second Amendment rights.